2014
DOI: 10.1039/c4bm00053f
|View full text |Cite
|
Sign up to set email alerts
|

The substrate-dependent regeneration capacity of mesenchymal stem cell spheroids derived on various biomaterial surfaces

Abstract: ADSC spheroids derived on various biomaterials present different in vitro properties, which may explain their different efficacies in cartilage repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Besides, our previous studies demonstrated that MSC spheroids formed on PVA membranes had lower stemness and differentiation capabilities than those on chitosan [57]. Transplantation of PVA-derived spheroids in a rabbit chondral defect model did not significantly improve the cartilage regeneration, compared to chitosan-derived spheroids [58]. Therefore, we suggested that FOXD3-transfected spheroids obtained from PVA may not be as useful as FOXD3-transfected spheroids obtained from chitosan in repairing the neural deficit of the zebrafish.…”
Section: Discussionmentioning
confidence: 90%
“…Besides, our previous studies demonstrated that MSC spheroids formed on PVA membranes had lower stemness and differentiation capabilities than those on chitosan [57]. Transplantation of PVA-derived spheroids in a rabbit chondral defect model did not significantly improve the cartilage regeneration, compared to chitosan-derived spheroids [58]. Therefore, we suggested that FOXD3-transfected spheroids obtained from PVA may not be as useful as FOXD3-transfected spheroids obtained from chitosan in repairing the neural deficit of the zebrafish.…”
Section: Discussionmentioning
confidence: 90%
“…MSCs grown on nonfouling hydrogel remained undifferentiated even after induction . Many hydrophilic material surfaces are nonadherent so cells are forced to form aggregates . On the current PU surface, cells attached prior to forming aggregates through cell assembly.…”
Section: Resultsmentioning
confidence: 93%
“…On the current PU surface, cells attached prior to forming aggregates through cell assembly. The self‐assembled aggregates are considered to be superior to forced aggregates . Moreover, the current PU can be conveniently processed for various biomedical applications .…”
Section: Resultsmentioning
confidence: 99%
“…Intercellular cadherin interaction regulates the cell-cell adhesion, cell migration, and multiple types of cell signaling by association with the actin filaments [72]. The up-regulated expression levels of N-cadherin and/or E-cadherin were observed in MSC spheroids formed by different scaffold-free 3D culture systems including hanging drop method and CS substrates, comparing to those cultured on TCPS [71,73], indicating the involvement of cadherin-mediated signaling in the formation of MSC spheroids. Meanwhile, the calcium ions were chelated by the CS substrates [73].…”
Section: Physical and Chemical Factors Affecting Cell Behaviors In Scmentioning
confidence: 93%
“…The up-regulated expression levels of N-cadherin and/or E-cadherin were observed in MSC spheroids formed by different scaffold-free 3D culture systems including hanging drop method and CS substrates, comparing to those cultured on TCPS [71,73], indicating the involvement of cadherin-mediated signaling in the formation of MSC spheroids. Meanwhile, the calcium ions were chelated by the CS substrates [73]. Combined with several findings mentioned above, we propose a mechanism of MSC spheroid formation on CS substrates.…”
Section: Physical and Chemical Factors Affecting Cell Behaviors In Scmentioning
confidence: 96%